Molecular structure of the allelic variants of (AAT)n microsatellite locus Du47D in the parthenogenetic species Darevskia unisexualis and bisexual parental species D. valentini and D. raddei - Korchagin, V. I; Tokarskaya, O. N (Russian journal of genetics, 2010)
Microsatellite repeats are one of the most widespread elements of the eukaryotic genome, but are poorly studied in species with clonal reproduction. PCR analysis and DNA sequencing were used to study the molecular structure of the allelic variants of microsatellite locus Du47D in the parthenogenetic species Darevskia unisexualis and its evolutionary ancestors, bisexual species D. raddei and D. valentini, of the genus Darevskia (Lacerta saxicola complex). Sequencing showed that the allelic variants of the D. unisexualis Du47D locus and the alleles of its D. raddei and D. valentini orthologs have a perfect microsatellite cluster structure, differ in number of ATT monomeric units, and have certain species-specific combinations of nucleotide substitutions, deletions, and insertions in the microsatellite-flanking DNA sequences. The Du47D alleles that the parthenogenetic species inherited from D. valentini or from D. raddei were identified.